2017
DOI: 10.2298/ciceq160722060b
|View full text |Cite
|
Sign up to set email alerts
|

Modification of functional quality of beer by using microencapsulated green tea (Camellia sinensis L.) and Ganoderma mushroom (Ganoderma lucidum L.) bioactive compounds

Abstract: Increasing interest in production of frequently consumed functional food products has focused the present study on implementation of microencapsulated Ganoderma mushroom and green tea bioactive compounds in beer production. Electrostatic extrusion assisted microencapsulation of green tea and Ganoderma extracts enabled production of particles ranging from 490 to 1000 ?m in size, with up to 75% of entrapped total polyphenols. Dried, powdered extracts, as well as microparticles encapsulating Ganoderma and green t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Other studies used fruits, seeds, fruit juices and byproducts, and fruit extracts are often used for making special beer assortments with various flavor, taste, and aroma (SALANTA et al, 2020;RICCI et al, 2019;ADAMENKO et al, 2020;DORDEVIC, et al, 2016;BELSCAK-CVITANOVIC et al, 2017;ADENUGA et al, 2010);and lastly, CUNhA et al (2021) developed American blond ale with fruity aromas (murici, cupuaçu, and cajá), and evaluated some quality parameters, such as density and alcohol content and ºBrix. The authors also assessed untrained consumers' acceptance of flavor and aroma attributes, and their findings revealed that the beers added with fruit had higher physicochemical parameters and scores concerning the attributes analyzed.…”
Section: Cunha Et Almentioning
confidence: 99%
“…Other studies used fruits, seeds, fruit juices and byproducts, and fruit extracts are often used for making special beer assortments with various flavor, taste, and aroma (SALANTA et al, 2020;RICCI et al, 2019;ADAMENKO et al, 2020;DORDEVIC, et al, 2016;BELSCAK-CVITANOVIC et al, 2017;ADENUGA et al, 2010);and lastly, CUNhA et al (2021) developed American blond ale with fruity aromas (murici, cupuaçu, and cajá), and evaluated some quality parameters, such as density and alcohol content and ºBrix. The authors also assessed untrained consumers' acceptance of flavor and aroma attributes, and their findings revealed that the beers added with fruit had higher physicochemical parameters and scores concerning the attributes analyzed.…”
Section: Cunha Et Almentioning
confidence: 99%
“…Beer made with mushroom extracts was also investigated, and while visual appearance and colour influenced other sensory aspects, this attribute has not been investigated [80]. Encapsulated G. lucidum extract added to beer, on the other hand, generated a more prominent and darker hue, making it more appealing to customers [81].…”
Section: Medicinal Mushroom Pigments In Food Productionmentioning
confidence: 99%
“…Beyond plants, roots, fruits, and flowers, mushrooms are emerging beer adjuncts, specifically, the mushroom Ganoderma lucidum [ 44 , 45 ]. This traditional Asian medicinal macrofungus has hundreds of distinct secondary metabolites with identified therapeutic potential [ 46 ].…”
Section: Potential Production Steps and Addiction Mechanism For Inclusion Of Brewing Adjunctsmentioning
confidence: 99%
“…As a result, when the scope of a traditional beer is extended and functional beers are characterized, specific physicochemical and stability analyses are demanded to corroborate its effectiveness. Within the set of most common tests found in the literature for functional beers are: total phenolic content [ 29 , 44 , 49 ], phenolic profile [ 29 ], antioxidant activity [ 27 , 50 , 51 ] and volatile profile [ 17 , 38 , 52 ]. Therefore, to evaluate the performance of the functional beers, the next sections will focus on the phenolic content and antioxidant activity of the beers.…”
Section: Evaluation Of Bioactive Compounds and Health Benefitsmentioning
confidence: 99%